2003
DOI: 10.1021/bi0342822
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Extended-Spectrum β-Lactamase Toho-1:  Insights into the Molecular Mechanism for Catalytic Reaction and Substrate Specificity Expansion,

Abstract: The crystallographic structure of the class A beta-lactamase Toho-1, an extended-spectrum beta-lactamase with potent activity against expanded-spectrum cephems, has been determined at 1.65 A resolution. The result reveals that the Lys73 side chain can adopt two alternative conformations. The predominant conformation of Lys73 is different from that observed in the E166A mutant, indicating that removal of the Glu166 side chain changes the conformation of the Lys73 side chain and thus the interaction between Lys7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 51 publications
(88 reference statements)
8
83
0
Order By: Relevance
“…In Toho-1, for instance, it has been proposed that the cefotaximase and ceftazidimase activities are partly explained by increased flexibility of the U loop and of the loop between B3 and B4, both part of the binding pocket. 15,19,20 Consistent with this view, there are fewer interactions between the U loop and the a/b domain of the CTX-M structures determined here, compared with TEM and SHV enzymes. Some of the hydrogen bonds connecting the N and C termini of the U loop are also lost in the CTX-M-like enzymes, such as the one between Thr160 (replaced by a phenylalanine) and Thr/Ser181 in non-ESBL b-lactamases.…”
Section: Active Sitesupporting
confidence: 84%
See 2 more Smart Citations
“…In Toho-1, for instance, it has been proposed that the cefotaximase and ceftazidimase activities are partly explained by increased flexibility of the U loop and of the loop between B3 and B4, both part of the binding pocket. 15,19,20 Consistent with this view, there are fewer interactions between the U loop and the a/b domain of the CTX-M structures determined here, compared with TEM and SHV enzymes. Some of the hydrogen bonds connecting the N and C termini of the U loop are also lost in the CTX-M-like enzymes, such as the one between Thr160 (replaced by a phenylalanine) and Thr/Ser181 in non-ESBL b-lactamases.…”
Section: Active Sitesupporting
confidence: 84%
“…Toho-1 has a lower hydrolytic activity against penicillins and higher hydrolytic activity against ceftazidime than the "typical" CTX-M enzymes. 15 Three other atypical CTX-M enzymes have also been reported that exhibit an unusually high level of resistance to ceftazidime. The improved activity versus ceftazidime for these three enzymes, CTX-M-15, 16 CTX-M-16 17 and CTX-M-27 18 is correlated with the substitution Asp240Gly, which has never been observed in naturally occurring TEM and SHV-type ESBLs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, one appreciates that the first common theme to emerge is that the active site is selectively "remodeled and expanded" to accommodate the bulky R 1 side chain of extendedspectrum cephalosporins [6]. This remodeling is observed in the atomic structures of Toho-1, TEM-52, TEM-64, the Gly238Ala ESBL in TEM, SHV-2, PER-1 and OXA-10 betalactamases [46][47][48][49][50][51][52]. Recently, the crystal structure of KPC-2 was determined, demonstrating modifications in the active site that allow access to carbapenems [53].…”
Section: Structural Properties Of Esblsmentioning
confidence: 99%
“…Finally, a hydrogen bond is formed between the Ser61 hydroxyl group O γ and the Ser122 hydroxyl group O γ (3.02 Ǻ). For class A β-lactamases, distances of 3.17 Å for PER-1 (1e25), 15 3.15 A for TEM-1 in 1.55 Å resolution structure (1zg4), 16 but 3.55 Å in 1.8 Å resolution structure (1btl), 17 and 2.89 Å in Toho-1 (1iys) 18 are found. In class A β-lactamases, the Lys73 δ-NH 2 group is hydrogen bonded to the carboxylate group of Glu166.…”
Section: Active Sitementioning
confidence: 96%